How does physicians' decisional conflict influence their ability to address treatment outcomes in a decision-making encounter with an advanced-stage cancer simulated patient? A descriptive study. Issue 9 (September 2020) - Libert, Yves; Peternelj, Livia; Canivet, Delphine; Farvacques, Christine; Liénard, Aurore; Ménard, Catherine; Merckaert, Isabelle; Reynaert, Christine; Slachmuylder, Jean-Louis; Razavi, Darius
Highlights: Physicians' decisional conflict interferes with their ability to address outcomes. Physicians' specific (not general) decisional conflict is predictive. Physicians' decisional conflict may impair the quality of a decision-making process. Physicians should address treatment outcomes according to patient preferences. Abstract: Objectives: This descriptive study assesses how physicians' decisional conflict influences their ability to address treatment outcomes (TOs) in a decision-making encounter with an advanced-stage cancer simulated patient (SP). Methods: Physicians (N = 138) performed a decision-making encounter with the SP trained to ask for TOs information. The physicians' decisional conflict regarding patients' cancer treatments in general was assessed with the General Decisional Conflict Scale (Gen-DCS). The physicians' decisional conflict regarding the SP's cancer treatments was assessed with the Specific Decisional Conflict Scale (Spe-DCS). Physicians' ability to address TOs during the encounter was assessed with an interaction analysis system: the Multi-Dimensional Analysis of Patient Outcome Predictions (MD.POP). Weekly time spent with cancer patients was assessed with a questionnaire. Results: Physicians' Spe-DCS (β = -.21 ; p = .014) and weekly time spent with cancer patients (β = .22 ; p = .008) predicted the number of TOs addressed during the encounter. Spe-DCS scores predicted nearly all MD.POP dimensions (r = -.18 ; p = .040 to r = -.30 to p < .001) whereas Gen-DCS scores predicted nearly none MD.POP dimensions. Conclusion: Physicians' specific decisional conflict interferes with their ability to address TOs in a decision-making encounter with an advanced-stage cancer SP. Practice implications: Physicians should be trained to address TOs according to patient preferences, despite their own decisional conflict.